2013
DOI: 10.3171/2013.7.jns13311
|View full text |Cite
|
Sign up to set email alerts
|

Methylation markers of malignant potential in meningiomas

Abstract: Object Although most meningiomas are benign, about 20% are atypical (Grade II or III) and have increased mortality and morbidity. Identifying tumors with greater malignant potential can have significant clinical value. This validated genome-wide methylation study comparing Grade I with Grade II and III meningiomas aims to discover genes that are aberrantly methylated in atypical meningiomas. Methods Patients with newly diagnosed meningioma were identified as part of the Ohio Brain Tumor Study. The Infinium Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…They profiled 19 WHO grade I, II and III meningiomas and similar with Vengoechea et al [74], Gao’s group looked for differences in methylation between benign and malignant meningioma groups. They concluded that WHO grade II and III meningiomas were globally hypomethylated compared to WHO grade I tumors but they did not offer much details and probe identification except for 15 hypomethylated genes that were further investigated for expression analysis.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…They profiled 19 WHO grade I, II and III meningiomas and similar with Vengoechea et al [74], Gao’s group looked for differences in methylation between benign and malignant meningioma groups. They concluded that WHO grade II and III meningiomas were globally hypomethylated compared to WHO grade I tumors but they did not offer much details and probe identification except for 15 hypomethylated genes that were further investigated for expression analysis.…”
Section: Discussionmentioning
confidence: 86%
“…With time, molecular advances allowed interrogation at a larger number of CpG loci [35] culminating with the methylation assays from Illumina (27k and 450k) interrogating approximately 27.000 and 450.000 CpG loci [74,21]. To the best of our knowledge only three studies addressed global methylation in meningiomas [35,74,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one study, authors explored the expression of pro-apoptotic and anti-apoptotic factors in 67 AAM patients, they found that low expression of CASP3 and BAX, and overexpression of survivin and MDM2 were associated with recurrence [33]. Additionally, methylation of PDCD1 and IGF2BP1 was found to correlate with increased malignant potential and associated with an aggressive phenotype [34]. Other cytogenetic alterations and specific gene mutations have been identified in patients with AAM that differ from those found in WHO grade I meningiomas [35].…”
Section: Discussionmentioning
confidence: 95%